Application of zircon typology method to felsic rocks (Cappadocia, Central Anatolia, Turkey): a zircon crystallization temperature perspective - Akin, Lütfiye; Schmitt, Axel Karl (Turkish journal of earth sciences, 2019)
Zircon typology was developed nearly half a century ago as a tool for constraining the thermochemical conditions in granitic magmas from the morphology of zircon prismatic and pyramidal crystal surfaces. Although the method precedes experimentally constrained zircon-based thermometers (zircon saturation, Ti-in-zircon), the morphology of zircon remains an important criterion for zircon studies commonly relying on visual recognition of crystals during sample purification via hand-picking. This may introduce selection bias if morphologically distinct zircon crystals are present in a population. We conducted a comparison between zircon typology and thermochemical constraints from zircon thermometry and whole rock compositions. Therefore, we focused on zircon populations from diverse volcanic rocks from the Central Anatolian Volcanic Province (CAVP), which erupted during the Upper Miocene to Quaternary in a continental environment in a postcollisional extensional regime. Neogene rhyolitic volcanism produced widespread pyroclastic rocks (ignimbrites, and subordinate fall-out deposits), which are interstratified with fluviolacustrine sediments and local lava flows originating from various volcanic centers in the region. Zircon crystals from Neogene ignimbrites are mostly intermediate-temperature, calc-alkaline hybrid type, whereas zircons from Quaternary rhyolitic domes/lavas fall into typology trends assigned to subalkaline mantle-type granites with low temperatures and high alkalinity indices. Trends in zircon saturation and zircon crystallization temperatures in CAVP ignimbrites are broadly consistent with typology temperature estimates, but temperature differences between these estimates are slightly higher or lower. However, these deviations may partly result from zircon typology relying on crystal shape, and thus the latest crystallization event, which could result in bias between the granitic rocks used for the original typology development and the volcanic rocks investigated here. Our results show that typology differences exist between zircon populations from both Miocene ignimbrites and Quaternary rhyolitic domes/lavas of the CAVP. These differences affect the temperature values obtained from zircon typologies that also correlate with conventional quantitative thermometric calculations.